AJARAN KAHARUDIN DI YAYASAN AL-MAGHFURULLAH KABUPATEN CIREBON, JAWA BARAT - Suhanah Suhanah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
This research employs case study method with qualitative approach. The purpose of this research is to figure out some information related to al-Maghfurullah Foundation cases consisting of: 1). Profile of al-Maghfurullah Foundation; 2). Its religious activities; 3). Chronology of al-Maghfurullah Foundation is considered as deviant religious teaching; 4). Government and stakeholders efforts in solving al-Maghfurullah Foundation cases. The result of research shows that Kaharudin as the leader of al-Maghfurullah Foundation and teacher undertakes some deviant religious teachings and practices that lead to social upheaval and issue Indonesian Ulema Council fatwa to handle development of Kaharudin’s teaching. It can be seen that no parties deal with this cases seriously, comprehensively, systematically, and continuously.